2023
DOI: 10.1021/acsnano.2c09838
|View full text |Cite
|
Sign up to set email alerts
|

[2,1,3]-Benzothiadiazole-Spaced Co-Porphyrin-Based Covalent Organic Frameworks for O2 Reduction

Abstract: Designing N-coordinated porous single-atom catalysts (SACs) for the oxygen reduction reaction (ORR) is a promising approach to achieve enhanced energy conversion due to maximized atom utilization and higher activity. Here, we report two Co(II)-porphyrin/ [2,1,3]-benzothiadiazole (BTD)-based covalent organic frameworks (COFs; Co@ rhm -PorBTD and Co@ sql -PorBTD), which are efficient SAC systems for O2 electrocatalysis (ORR). Experimental results demonstrate that these two COFs outperform the mass activity (at 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 89 publications
0
17
0
Order By: Relevance
“…Recently, Bhunia et al reported two Co(II) COFs, Co@rhm-PorBTD and Co@sql-PorBTD, by compensating for the porphyrinic units with two different benzothiadiazole groups to introduce heteroatoms S and N (Figure 8a). 55 Highly crystalline structures were confirmed by PXRD patterns (Figure 8b) and TEM images. Their ORR performances were tested by cyclic voltammetry (CV) and linear-sweep voltammetry analyses.…”
Section: Cof-based Sacs For Electrocatalytic Energy Applicationsmentioning
confidence: 88%
See 2 more Smart Citations
“…Recently, Bhunia et al reported two Co(II) COFs, Co@rhm-PorBTD and Co@sql-PorBTD, by compensating for the porphyrinic units with two different benzothiadiazole groups to introduce heteroatoms S and N (Figure 8a). 55 Highly crystalline structures were confirmed by PXRD patterns (Figure 8b) and TEM images. Their ORR performances were tested by cyclic voltammetry (CV) and linear-sweep voltammetry analyses.…”
Section: Cof-based Sacs For Electrocatalytic Energy Applicationsmentioning
confidence: 88%
“…39 For example, COFs using different monomers may result in different packing densities when anchoring atomic metals, which is critical for catalytic performance. 55 However, due to monomer solubility, sometimes COF structures cannot be synthesized directly and require post-treatments such as linkage interconversion. Taking the example of imine linkages, they can be transformed into amide, amine, thioazole, oxazole, quinoline, and protonated imine linkages through oxidation, reduction, molten sulfur, monomer exchange, protonation, etc., respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzothiadiazole is one of the representative electron-deficient groups and has been widely used to synthesize frameworks, such as COFs 40–45 and metal–organic frameworks (MOFs). 46 For example, benzothiadiazole-based 2D imine-linked COFs were reported by Liu et al as efficient heterogeneous photocatalysts for organic transformation under visible light.…”
Section: Introductionmentioning
confidence: 99%
“…39 Besides these aforementioned applications, Liu et al synthesized sp 2 c-and imine-linked COFs using a three-component synthesis method, which exhibits higher hydrogen production activity compared with two-component COFs. 7 Benzothiadiazole is one of the representative electrondeficient groups and has been widely used to synthesize frameworks, such as COFs [40][41][42][43][44][45] and metal-organic frameworks (MOFs). 46 For example, benzothiadiazole-based 2D imine-linked COFs were reported by Liu et al as efficient heterogeneous photocatalysts for organic transformation under visible light.…”
Section: Introductionmentioning
confidence: 99%